2006
DOI: 10.1080/15421400601013411
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Betaine-30 Dispersed in Polymeric Solids

Abstract: Emission spectra and excitation emission matrix of Betaine-30 (B30) dispersed in polymeric solids were determined. Emission wavelength was different for each polymer. The maximum wavelength became long with increasing the polarity of the polymer. A new possibility to determine the polarity of the medium using B30 was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…To rationalize the behavior of B30 and its sensitivity against even small changes in its molecular-microscopic environment, this class of zwitterionic dyes has been repeatedly and intensively studied. ,, Nevertheless, the perichromism of these betaine dyes is far from being well understood. New findings with respect to their solvatochromic, thermochromic, photophysical, ,, and structural behavior have been recently reported; some of them will be commented on in this work.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…To rationalize the behavior of B30 and its sensitivity against even small changes in its molecular-microscopic environment, this class of zwitterionic dyes has been repeatedly and intensively studied. ,, Nevertheless, the perichromism of these betaine dyes is far from being well understood. New findings with respect to their solvatochromic, thermochromic, photophysical, ,, and structural behavior have been recently reported; some of them will be commented on in this work.…”
Section: Introductionmentioning
confidence: 90%
“…With respect to the strong solvatochromism of B30 , its fluorosolvatochromism would be also of interest. Whereas solutions of B30 do not exhibit any fluorescence at room temperature, it was shown quite recently for the first time that B30 shows indeed fluorescence at low temperatures. , Kharlanov and Rettig demonstrated that solutions of B30 in 1-chlorobutane and ethanol exhibit fluorescence in both solvents at 77 K, which is absent at room temperature. Yoshida et al reported that B30 , dispersed in thin polymer films (e.g., PVA, PMMA, and PS), shows luminescence at 77 K and even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-state approximation proves to be adequate for the studied system, and allowed the observed solvent-polarity-induced decrease of the 2PA cross-section to be related to the decrease of the transition moment and the increase in the excitation energy. Noteworthy examples are the detection of a narrowing of the CT absorption band in the temperature range of 10-293 K, [66] low-temperature fluorescence, [40,72,73] or room-temperature fluorescence in the subpicosecond regime. [17,52,53] More recently, RD has gained interest as a material used for model studies of controlled drug delivery [54,55] and as a promising agent for comparing the electrophilicity of various neutral Lewis acidic species.…”
Section: Introductionmentioning
confidence: 99%
“…[1, 15-17, 38, 50, 70, 71] To date, a large variety of spectroscopic issues concerning RD and its surroundings have been addressed. Noteworthy examples are the detection of a narrowing of the CT absorption band in the temperature range of 10-293 K, [66] low-temperature fluorescence, [40,72,73] or room-temperature fluorescence in the subpicosecond regime. [78] As mentioned above and discussed in our previous works, [21,35,101] solvatochromism may also be considered in the context of 2PA for molecules in solution.…”
Section: Introductionmentioning
confidence: 99%